New insights into hepatitis B virus lymphotropism: Implications for HBV-related lymphomagenesis - Svicher, Valentina; Salpini, Romina; D’Anna, Stefano; Piermatteo, Lorenzo; Iannetta, Marco; Malagnino, Vincenzo; Sarmati, Loredana (Frontiers in Oncology, 2023)
HBV is one of the most widespread hepatitis viruses worldwide, and a correlation between chronic infection and liver cancer has been clearly reported. The carcinogenic capacity of HBV has been reported for other solid tumors, but the largest number of studies focus on its possible lymphomagenic role. To update the correlation between HBV infection and the occurrence of lymphatic or hematologic malignancies, the most recent evidence from epidemiological and in vitro studies has been reported. In the context of hematological malignancies, the strongest epidemiological correlations are with the emergence of lymphomas, in particular non-Hodgkin’s lymphoma (NHL) (HR 2.10 [95% CI 1.34-3.31], p=0.001) and, more specifically, all NHL B subtypes (HR 2.14 [95% CI 1.61-2.07], p<0.001). Questionable and unconfirmed associations are reported between HBV and NHL T subtypes (HR 1.11 [95% CI 0.88-1.40], p=0.40) and leukemia. The presence of HBV DNA in peripheral blood mononuclear cells has been reported by numerous studies, and its integration in the exonic regions of some genes is considered a possible source of carcinogenesis. Some in vitro studies have shown the ability of HBV to infect, albeit not productively, both lymphomonocytes and bone marrow stem cells, whose differentiation is halted by the virus. As demonstrated in animal models, HBV infection of blood cells and the persistence of HBV DNA in peripheral lymphomonocytes and bone marrow stem cells suggests that these cellular compartments may act as HBV reservoirs, allowing replication to resume later in the immunocompromised patients (such as liver transplant recipients) or in subjects discontinuing effective antiviral therapy. The pathogenetic mechanisms at the basis of HBV carcinogenic potential are not known, and more in-depth studies are needed, considering that a clear correlation between chronic HBV infection and hematological malignancies could benefit both antiviral drugs and vaccines.